2009
DOI: 10.1074/jbc.m109.036285
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp90 Inhibitor Geldanamycin Abrogates Colocalization of eIF4E and eIF4E-Transporter into Stress Granules and Association of eIF4E with eIF4G

Abstract: The eukaryotic translation initiation factor eIF4E plays a critical role in the control of translation initiation through binding to the mRNA 5 cap structure. eIF4E is also a component of processing bodies and stress granules, which are two types of cytoplasmic RNA granule in which translationally inactivated mRNAs accumulate. We found that treatment with the Hsp90 inhibitor geldanamycin leads to a substantial reduction in the number of HeLa cells that contain processing bodies. In contrast, stress granules ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
5
28
0
3
Order By: Relevance
“…In addition, components of the R2TP-Hsp90 complex, which has a role in assembling multi-molecular protein complexes involved in gene expression, were confirmed as Hsp90 clients [61]. These observations, as well as a slow and sustained mild decrease of proteins identified in our stSILAC analysis as taking part in post-transcriptional control processes, attest to an Hsp90-mediated regulatory role in the control of gene expression [58], [60], [62], [63].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, components of the R2TP-Hsp90 complex, which has a role in assembling multi-molecular protein complexes involved in gene expression, were confirmed as Hsp90 clients [61]. These observations, as well as a slow and sustained mild decrease of proteins identified in our stSILAC analysis as taking part in post-transcriptional control processes, attest to an Hsp90-mediated regulatory role in the control of gene expression [58], [60], [62], [63].…”
Section: Discussionsupporting
confidence: 69%
“…We found that Ago1 was destabilized upon RNAi-mediated knockdown (KD) of the miRNA biogenesis factor Drosha in Drosophila S2 cells compared with mock (LacZ) KD ( Figures 1A and S1), consistent with previous work (Smibert et al, 2013). In addition, we blocked miRNA loading into Ago1 by treating S2 cells with the Hsp90 chaperone inhibitor 17-(Allylamino)-17-demethoxygeldanamycin (17-AAG) Schulte and Neckers, 1998) and observed Ago1 destabilization ( Figure 1B), as reported previously in mammals (Johnston et al, 2010;Suzuki et al, 2009).…”
Section: Selective Ubiquitination Of Empty Drosophila Ago1supporting
confidence: 74%
“…Depletion of Drosha or Dcr-1 induces degradation of Ago1 in Drosophila (Smibert et al, 2013). Moreover, treatment with Hsp90 inhibitors, which block the loading of miRNA/miRNA* duplexes into AGO , destabilizes mammalian AGO (Johnston et al, 2010;Suzuki et al, 2009). Thus, selective degradation of empty AGO is evolutionarily conserved, strongly implying that it is significant for miRNA function.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that RBM45, an RNA binding protein whose levels are increased in the CSF of ALS patients 72 , forms cytoplasmic inclusions in motor neurons and glia of ALS patients. Similarly, we now show that increased levels of the stress-granule associated 74 eIF4E transporter protein (4e-T) in the CSF of sALS patients correlate with its presence in p62-positive nuclear granules and cytoplasmic inclusions (Figure S-2). Intranuclear inclusions are a pathological feature of sALS 99,100 and we demonstrate the presence of a transport protein, 4e-T, in these inclusions.…”
Section: Discussionsupporting
confidence: 61%